ダイ17ジ ナンキョク チイキ カンソクタイ エットウタイ ホウコク 1976-1977 - 芳野, 赳夫; ヨシノ, タケオ; Yoshino, Takeo (1981)
P(論文) 17次越冬隊員29名は, 1976年2月1日から1年間昭和基地, 5月以降はみずほ基地を加えて, 国際磁気圏観測(IMS)に関連した観測を重点的に行った。昭和基地では極光, 地磁気, 電離層, 気象, 地震, 潮汐の定常観測のほか, IMSのための観測機器の増設, 人工衛星追尾受信装置の建設を行い, 人工衛星受信, 7基(2基は夏期間)のロケット打ち上げと, 1基の大気球観測などの超高層部門の重点観測が行われ, 気象・医学の研究も行われた。みずほ基地は, IMSのための超高層観測を開始するため, 4月に観測棟1棟の建設と16kVA発電機の増設を行い, 5月14日以降4名が通年滞在し, 超高層のほか, 雪氷, 地上気象の観測を行い, 特に超高層部門の多点観測に貢献した。 Twenty-nine members of the wintering party occupied Syowa Station from February 1,1976 to January 31,1977,carrying out the preparation and observations in accordance with the program of the first year of research projects of the International Magnetospheric Study (IMS). At Syowa Station, in addition to the observation of aurora, geomagnetism, ionosphere, meteorology, seismology, marine morphology, ocean tide, and medical science, the major research program covers the preparation of many observation apparatuses for upper atmosphere physics, as well as the construction of satellite tracking and telemetry facilities, the reception of telemetry signals from scientific satellites, and the launching of seven (five in winter) sounding rockets and one big balloon to carry out the IMS project. Mizuho Station was improved for upper atmospheric observations in connection with the IMS program including the construction of one observation hut and the setting up of a 16kVA generator in May 1976,and occupied by four members in rotation so as to carry out observations of upper atmosphere physics, glaciology, and meteorology from May 14,1976 to January 26,1977. departmental bulletin paper